ANALISIS PENGEMBANGAN EKONOMI KREATIF BERBASIS KEARIFAN LOKAL KHAS SUKU DAYAK - Sinaga, Hotmiana; Eriawaty, Eriawaty; Putri, Windy Utami (STKIP Persada Khatulistiwa Sintang, 2024)
Tribe ofÂ Â have their own habits in managing nature and the environment. These habits formed into a local wisdom. Local wisdom contains universal or comprehensive values seen in everyday life in society, so it's not surprising that a lot of local wisdom has the opportunity to develop into creative industries by adding creativity and innovation, so the purpose of this research is to find out the development of the creative economy based on local wisdom typical of the tribe of the Dayak in the Borneo Accessories City of Palangka Raya.This research uses a qualitative approach with case study methods. The informant of this study is the owner of Borneo Accessories City Palangka Raya business as distributor and supplier. The study was conducted from 1 February to April 25, 2024. The other informant as a supporter is the Mrs. Karlina Batik, as head of the deposit room Disbudpar Kalteng. Interviewing as a primary data collection technique, observation, and documentation as a supporting data collection tool. Results of the research found in this study are that the products produced in Borneo Accessories City Palangka Raya are very diverse ranging from customary clothes, properties to accessories. And for the production process still more to use traditional methods in line with the customs of the past. For its products especially customary clothing has undergone a lot of development in terms of materials and shapes. measures to develop a creative economy based on local wisdom by attending national events in Central Kalimantan and outside the province, conducting routine online and offline promotions, making product variations, ensuring availability of raw materials for processing and production of products, prioritizing product quality, and adjusting price to quality, distributing products, supplying products.